MEDIA PEMBELAJARAN PENGENALAN ANATOMI TUBUH MANUSIA BERBASIS GAME LEARNING (STUDI KASUS: YAYASAN DHARMA BHAKTI KESEJAHTERAAN SOSIAL AMAL MULIA) - Neferly Arif Budiman; Desi Andreswari; Funny Farady Coastera (Rekursif: Jurnal Informatika, 2026)
Learning human anatomy is often considered difficult for students to understand, especially for those with special needs such as intellectual disabilities (tuna grahita), due to the abstract nature of the material and the limited availability of visual learning tools. This study aims to design and develop an interactive and engaging learning media based on Game Learning to improve students' understanding of human body systems, including the respiratory, digestive, and circulatory systems. The research employed the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The participants in this study were eighth-grade students at a Special Needs Junior High School (SLB). Data were collected through observation, interviews, validation questionnaires, as well as pre-test and post-test assessments. The validation results indicate that the developed media is highly feasible for use. In addition, usability testing using the System Usability Scale (SUS) produced an average score of 58.89, indicating that the media was well-received by users. Statistical analysis using an independent sample t-test also showed a significant improvement in students' understanding after using the game. Therefore, this game-based learning media proves to be effective in helping students grasp human anatomy material more easily and enjoyably.